Prospective assessment of the aquaculture sector : national policies and environmental impacts - Bohnes, Florence Alexia (Nanyang Technological University, 2020)
The demand for food is rising due to a growing world population and increasing wealth, requiring a significant increase of food production globally. This needs to happen in a sustainable manner, and aquaculture (i.e. seafood farming) appears like a promising solution, as it is associated to more environmental-friendly production than other animal protein sources and to a significant growth potential. However, most of the aquaculture growth policies implemented in the recent decades have failed due to an insufficient anticipation of the policies environmental and socioeconomical implications at large. This PhD project participated to tackle this problem and produced a framework to assess the current and future environmental sustainability of aquaculture growth policies, i.e. to anticipate the implications of these policies in terms of environmental impacts and therefore support policy-makers in making more environmental-friendly policies. Scenarios of aquaculture development were thus built using an economic model to ensure economic viability, after which the environmental impacts of these scenarios were quantified using life cycle assessment. The framework was applied on two case studies: (i) the implementation of the “30-by-30” policy in Singapore and (ii) the diversification of the aquaculture sector in terms of species and technologies in Norway, both until 2040. Based on the results of the case studies, recommendations for policy-makers were established and specific reductions of environmental impacts in the aquaculture sector were advocated, such as which technologies and species to prioritize and which feed options to encourage.